The Enlightenment : A brief history with documents - Jacob, Margaret C. (Boston Bedford/St. Martin's, 2017)
Gain insight into The Enlightenment from the era's most influential thinkers as Enlightenment explores the impact this time period had on the political, religious, and educational landscape of the day.
Includes bibliographies and index
Keywords: Tham khảo